Concepts for open systems cooperation in distributed CIM-structures - Tschammer, V.; Eckert, K.P.; Henckel, L. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
The authors report on innovative computer-integrated manufacturing structures, based on future communication techniques (optical fiber networks combined with broadband transmission techniques) and novel concepts of distributed computing, that are currently being investigated by the BERCIM project. Basic ideas and design principles for open systems cooperation in distributed CIM structures are presented. The development of a basic architecture and general principles of integration, the inclusion of service qualities, the selection of transport protocols and services, and the development of application structures are discussed. Related problems within the framework of BERKOM, a pilot project of the German PTT for broadband-ISDN, are investigated.< >